Tunnel-type manganese-based oxide positive electrode material and preparation method and application thereof
Patent Information
- Application Number
- CN202611056607.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-16
- Publication Date
- 2026-10-30
AI Technical Summary
[0003]然而,传统方法制备的Na0.44MnO2材料存在严重的首周充电容量低这一本征缺陷,极大地制约了其实际应用;该材料理论可脱出的钠离子约为0.44mol,对应理论充电容量约121mAh/g;但在实际电化学过程中,由于材料内部存在电化学惰性的隧道位点,即部分钠离子被锁定在结构中的特定位置而无法脱出,导致首周实际可脱出的钠离子仅有约0.22mol,首周充电容量通常仅为60mAh/g左右;在以正极作为唯一钠源的全电池体系中,这一缺陷会直接拉低全电池的可用容量,迫使制造商不得不采用复杂的预钠化工艺进行补偿,从而显著增加了电池的制造成本和工艺难度
[0020]本发明提出一种隧道型锰基氧化物正极材料及其制备方法与应用,其核心创造性在于通过拓扑重构策略,实现了隧道结构内离子占位的精准调控,具体为氢离子(H+)占据电化学惰性隧道位点,而将具有电化学活性的S形隧道位点完全交由钠离子(Na+)占据;这一独特的晶体学构型,解决了传统Na0.44MnO2材料中因钠离子占据惰性位点而形成死钠、无法脱出导致首周充电容量低下的技术难题;基于此结构,本发明的正极材料首周充电容量得到提升,从传统材料的约60mAh/g一举提升至不低于100mAh/g,首次充分释放了该材料的理论潜力;同时,材料在保有隧道结构固有高倍率性能优势的基础上,其长循环稳定性也得到显著增强,实现了高容量、高倍率与长寿命的协同提升。
Smart Images

Figure CN123017957A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of sodium-ion battery cathode material technology, specifically relating to a tunnel-type manganese-based oxide cathode material, its preparation method, and its application. Background Technology
[0002] Due to the scarcity and uneven geographical distribution of lithium resources, sodium-ion batteries, with their advantages of abundant sodium reserves and low cost, have become a promising alternative technology in the field of large-scale energy storage grids. Among many cathode material systems, manganese-based oxides (Na₂O₃) are particularly promising. x MnO2 has attracted much attention due to its abundant manganese resources, environmental friendliness, and high thermal stability; among them, Na, which has a tunnel structure, is particularly noteworthy. 0.44 MnO2 materials, due to their rigid three-dimensional framework structure, can effectively resist lattice strain during sodium ion insertion / extraction, exhibiting excellent long-cycle structural stability, and are regarded as a class of cathode materials with great commercial potential.
[0003] However, Na prepared by traditional methods 0.44 MnO2 materials suffer from a severe intrinsic defect of low initial charge capacity, which greatly restricts their practical applications. Theoretically, the material can release approximately 0.44 mol of sodium ions, corresponding to a theoretical charge capacity of about 121 mAh / g. However, in actual electrochemical processes, due to the presence of electrochemically inert tunnel sites within the material—meaning some sodium ions are locked in specific locations within the structure and cannot be released—the actual amount of sodium ions that can be released in the first week is only about 0.22 mol, resulting in an initial charge capacity typically around 60 mAh / g. In full-cell systems where the cathode is the sole sodium source, this defect directly reduces the usable capacity of the entire battery, forcing manufacturers to employ complex pre-sodiuming processes to compensate, thus significantly increasing manufacturing costs and process complexity. Although the industry has attempted to improve capacity by increasing the intrinsic sodium content or introducing transition metal doping, the former easily leads to the collapse of the tunnel structure into a layered phase, and the latter has failed to alter the electrochemical activity of the sodium sites, making it difficult to break through 80 mAh / g in the first week.
[0004] Therefore, without compromising the stability of the tunnel structure, how to activate the electrochemically inert sodium sites in traditional materials and fully release Na+ is a crucial question. 0.44 The theoretical capacity of MnO2 and the solution to the technical problem of low initial charging capacity are key issues that urgently need to be addressed in this field. Summary of the Invention
[0005] The purpose of this invention is to overcome the shortcomings of the prior art and provide a tunnel-type manganese-based oxide cathode material, its preparation method and application.
[0006] To achieve the above objectives, the present invention provides the following technical solution:
[0007] This application provides a tunnel-type manganese-based oxide cathode material with the chemical composition Na. 0.44 MnO2, the cathode material has a tunnel structure, in which hydrogen ions (H+)... + Sodium ions (Na) occupy electrochemically inert tunneling sites. + It occupies the S-shaped tunneling sites that are electrochemically active.
[0008] Optionally, the cathode material has a first-week charging capacity of not less than 100mAh / g at a 0.1C rate.
[0009] Optionally, the discharge specific capacity of the cathode material after 350 cycles at 1C is not less than 85mAh / g.
[0010] A method for preparing the above-mentioned tunnel-type manganese-based oxide cathode material includes the following steps:
[0011] S1. Water-soluble manganese salt and thiosulfate are dissolved in water to form a mixed solution, and the reaction is carried out under microwave radiation. After the reaction is completed, the precipitate is separated, washed and dried to obtain γ-MnO2 precursor.
[0012] S2. The γ-MnO2 precursor is ground and mixed with a sodium source, and then calcined at 800℃~1000℃ in an oxygen-containing atmosphere. After cooling, the cathode material is obtained.
[0013] Optionally, in step S1, the water-soluble manganese salt is manganese sulfate monohydrate and manganese chloride, the thiosulfate is sodium thiosulfate, and the molar ratio of the water-soluble manganese salt to the thiosulfate is 1:(0.8-1.2); in step S2, the sodium source is sodium carbonate, and the molar ratio of the γ-MnO2 precursor to sodium carbonate is 1:(0.18-0.22).
[0014] Optionally, in step S1, the microwave reaction temperature is 80℃~150℃, and the reaction time is 1~30min; in step S2, the calcination temperature is 800℃~1000℃, the calcination time is 4~12h, and the heating rate is 1~10℃·min. -1 .
[0015] Optionally, the γ-MnO2 precursor obtained in step S1 contains hydrogen ions; H+ ions are generated during the calcination process in step S2. + / Na + Topological reconstruction due to site competition leads to H in the final product + Selectively occupying electrochemically inert tunneling sites, Na + S-shaped tunneling sites occupying electrochemical activity.
[0016] In step S1, the washing is performed by sequentially washing with deionized water and anhydrous ethanol, and the drying is performed by vacuum drying at 60℃~100℃ for 6~24h.
[0017] A sodium-ion battery positive electrode sheet comprises the above-mentioned positive electrode material, carbon black conductive agent and polyvinylidene fluoride binder, wherein the positive electrode sheet is prepared by mixing the positive electrode material, carbon black and polyvinylidene fluoride in N-methylpyrrolidone to form a slurry.
[0018] A sodium-ion battery includes a positive electrode, a metallic sodium negative electrode, and an electrolyte, wherein the positive electrode comprises the aforementioned positive electrode sheet.
[0019] Compared with the prior art, this application has the following beneficial effects:
[0020] This invention proposes a tunnel-type manganese-based oxide cathode material, its preparation method, and its application. Its core innovation lies in achieving precise control of ion occupancy within the tunnel structure through a topological reconstruction strategy, specifically controlling the ion occupancy of hydrogen ions (H+). + The sodium ion occupies the electrochemically inert tunneling sites, while completely exchanging the electrochemically active S-shaped tunneling sites for sodium ions (Na+). + This unique crystallographic configuration, occupying a specific position, solves the problem of traditional Na+ crystals. 0.44 The technical challenge of low first-cycle charging capacity in MnO2 materials is that sodium ions occupy inert sites, forming dead sodium that cannot be extracted. Based on this structure, the first-cycle charging capacity of the cathode material of this invention is improved from about 60 mAh / g of traditional materials to no less than 100 mAh / g, fully releasing the theoretical potential of the material for the first time. At the same time, while maintaining the inherent high-rate performance advantage of the tunnel structure, the long-cycle stability of the material is also significantly enhanced, achieving a synergistic improvement in high capacity, high rate and long life. Attached Figure Description
[0021] Figure 1 This is the XRD pattern of the product of this invention.
[0022] Figure 2 These are scanning electron microscope images of product embodiments and comparative examples of the present invention.
[0023] Figure 3 This is a comparison chart of the rate test results of the cathode material in this embodiment and the comparative example.
[0024] Figure 4 This is a comparison chart of the first-week charging capacity of the cathode material in this embodiment and the comparative example at a 0.1C rate.
[0025] Figure 5 This is a comparison chart of the long-cycle test of the cathode material in the embodiment of the present invention and the comparative example at a 1C rate. Detailed Implementation
[0026] The technical solutions of the present invention will be clearly and completely described below with reference to the accompanying drawings of the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0027] Furthermore, in this invention, an element referred to as fixed to or disposed on another element may be directly disposed on the other element, or there may be an intermediate element; when an element is considered to be connected to another element, it may be directly connected to the other element, or there may be an intermediate element at the same time; the terms vertical, horizontal, left, right and similar expressions used herein are for illustrative purposes only and do not represent the only implementation.
[0028] Example 1
[0029] This embodiment provides a method via H + / Na + The specific steps of the method for preparing tunnel-type manganese-based oxides using a site-competitive topological reconstruction strategy are as follows:
[0030] S1. Sodium thiosulfate, manganese sulfate monohydrate, and manganese chloride were dissolved in 150 mL of deionized water at a molar ratio of 1:0.5:0.5. The solution was magnetically stirred for 30 min at room temperature to form a homogeneous solution. The solution was then transferred to a microwave reactor and reacted under microwave radiation at 100 °C for 5 min. After the reaction was completed, the precipitate was collected by vacuum filtration and washed three times each with deionized water and anhydrous ethanol to remove residual impurities. The washed precipitate was then dried in a vacuum oven at 80 °C for 12 h to obtain the γ-MnO2 precursor.
[0031] S2. The dried γ-MnO2 precursor and sodium carbonate were thoroughly ground and mixed in an agate mortar at a molar ratio of 1:0.22; the mixture was then placed in a corundum crucible and placed in a muffle furnace at 5℃·min. -1 The heating rate was increased to 900℃, and calcination was carried out in air for 6 hours. After calcination, the furnace was allowed to cool naturally to room temperature to obtain the target product Na. 0.44 MnO2.
[0032] See Figures 1-5 This application provides a tunnel-type manganese-based oxide with the chemical composition Na. 0.44 MnO2, a tunnel-type manganese-based oxide, possesses a tunnel structure in which hydrogen ions (H+)... + Sodium ions (Na) occupy electrochemically inert tunneling sites. +It occupies the S-shaped tunneling sites that are electrochemically active.
[0033] The chemical composition of the product obtained in the above embodiments is Na. 0.44 The X-ray diffraction test results for MnO2 are attached. Figure 1 As shown, Figure 1 The X in the text refers to the general chemical formula Na. x The stoichiometric coefficient of sodium (Na) in MnO2, which is the atomic ratio of sodium to manganese in this tunnel-type manganese-based oxide material; for example Figure 1 As shown, the product diffraction peaks are similar to those of Na. 0.44 The MnO2 standard card showed a perfect match, with no impurity peaks, indicating the formation of a tunnel-type crystal structure; scanning electron microscope images are attached. Figure 2 As shown, the product has a uniform rod-shaped morphology and uniform size.
[0034] This material differs from traditional Na. 0.44 The core structural feature of MnO2 lies in: hydrogen ions (H+) + ) occupy electrochemically inert tunneling sites, while sodium ions (Na) + The S-shaped tunneling sites occupy electrochemically active sites; this configuration originates from the H+ generated during the preparation process. + / Na + Site competition topological reconstruction; in step S1, the microwave reaction promotes the decomposition of deionized water to produce H. + This enriches the generated γ-MnO2 precursor with H. + In step S2, during the high-temperature calcination stage, the precursor reacts with sodium carbonate in a solid-state reaction, H... + with Na + Site competition unfolds within the tunnel structure; due to H + With a smaller ionic radius, H exhibits a stronger binding affinity to electrochemically inert tunneling sites. + They preferentially occupy these inert sites and pin them stably, thereby forcing Na to... + All of them are concentrated in the electrochemically active S-shaped tunnel; the entire transformation process achieves the redistribution of ion sites while maintaining the topological configuration of the tunnel structure; this unique crystallographic configuration eliminates the non-ejectable sodium ions (i.e., dead sodium) that exist at inert sites in traditional materials at the atomic level, providing a structural basis for improving electrochemical performance.
[0035] In one specific embodiment, the cathode material has a first-cycle charging capacity of not less than 100 mAh / g at a 0.1C rate; and a discharge specific capacity of not less than 85 mAh / g after 350 cycles at a 1C rate.
[0036] Cyclic and rate performance tests were performed on the products of the examples:
[0037] Long-cycle testing was conducted at 1C rate, and the results are shown in the attached figure. Figure 5 As shown, Figure 5 In this context, H-NMO represents the tunnel-type manganese-based oxide cathode material (i.e., Na₂O₃) prepared in Example 1 of this invention. 0.44 MnO2's core characteristic is the presence of hydrogen ions (H+). + Occupying electrochemically inert sites (H represents Hydrogen); Na-NMO represents the conventional tunnel-type manganese-based oxide cathode material prepared in Comparative Example 1 (i.e., Na prepared by the conventional solid-state method). 0.44 MnO2 (sodium ions randomly occupying sites, Na represents Sodium); 1C=120mA / g means that the actual current density corresponding to the material at a 1C rate is 120mA / g; the horizontal axis represents the number of battery charge-discharge cycles (N); the vertical axis represents the specific capacity (mAh / g) represents the amount of electricity that can be released per gram of cathode material; combined with Figure 5 As can be seen, the discharge specific capacity of the product in the example after 350 cycles is 90.5 mAh / g, which meets the requirement of not less than 85 mAh / g; in stark contrast, the capacity of the comparative example has decayed to 23.5 mAh / g after 350 cycles; the excellent cycle stability of the product in the example is due to its unique ion site configuration: H + It plays a pinning and stabilizing role at inert tunnel sites, enhances the structural rigidity of the tunnel skeleton during repeated sodium insertion and extraction processes, and effectively suppresses lattice strain and structural degradation during the cycling process.
[0038] In rate performance testing, the products of the examples exhibited excellent capacity retention at different current densities; as shown in the attached figure. Figure 3 As shown in the figure, H-NMO represents the cathode material prepared in the embodiments of the present invention, that is, through H... + / Na + Hydrogen ions (H+) obtained by site-competitive topological reconstruction + Tunneling manganese-based oxides (Na₂O₃) occupying electrochemically inert tunneling sites 0.44 MnO2), where H represents the doped / occupied hydrogen ions; Na-NMO represents the conventional cathode material prepared in Comparative Example 1, i.e., Na prepared by the conventional solid-state method (oxalic acid method). 0.44 In MnO2 materials, sodium ions occupy all sites (including inert sites); the labeled 0.1C, 0.2C, 0.5C, 1C, 2C, and 5C represent the battery charge / discharge rate (C-rate), indicating the speed of charging or discharging; the horizontal axis (X-axis) represents the number of cycles (N), indicating the number of charge / discharge cycles; the vertical axis (Y-axis) represents the specific capacity (mAh / g), indicating the amount of electricity that can be released per unit mass of cathode material. A higher value on the vertical axis indicates a higher capacity; combined with... Figure 3As can be seen, at a high rate of 5C, the discharge specific capacity can reach 74.7 mAh / g, meeting the requirement of not less than 70 mAh / g; the inherent three-dimensional ion transport channels of the tunnel structure ensure the rapid migration of sodium ions, while H... + Stable occupancy of inert sites ensures the structure remains intact during high-rate sodium insertion / extraction, achieving a synergistic improvement in high capacity, high rate, and long lifetime.
[0039] A method for preparing tunnel-type manganese-based oxide cathode materials includes the following steps:
[0040] S1. Water-soluble manganese salt and thiosulfate are dissolved in water to form a mixed solution, and the reaction is carried out under microwave radiation. After the reaction is completed, the precipitate is separated, washed and dried to obtain γ-MnO2 precursor.
[0041] S2. The γ-MnO2 precursor is ground and mixed with a sodium source, and then calcined at 800℃~1000℃ in an oxygen-containing atmosphere. After cooling, the cathode material is obtained.
[0042] Step S1 uses water-soluble manganese salt and thiosulfate as raw materials to prepare γ-MnO2 precursor via microwave-assisted reaction. Compared with traditional hydrothermal or precipitation methods, microwave radiation can achieve rapid and uniform heating, completing the reaction within 5 minutes, significantly improving the precursor preparation efficiency. Step S2 mixes sodium source with γ-MnO2 precursor and calcines at high temperature in an oxygen-containing atmosphere. The air atmosphere provides sufficient oxygen to ensure that manganese ions maintain the required oxidation state, which is conducive to the stable formation of tunnel structures. Within the calcination temperature range of 800℃ to 1000℃, the precursor and sodium source can fully undergo solid-phase reaction to generate the target tunnel structure product. The entire preparation process requires only two steps, with a simple process route, mild conditions, and easy industrial production.
[0043] In one specific embodiment, in step S1, the water-soluble manganese salt is manganese sulfate monohydrate and manganese chloride, the thiosulfate is sodium thiosulfate, and the molar ratio of the water-soluble manganese salt to the thiosulfate is 1:(0.8-1.2); in step S2, the sodium source is sodium carbonate, and the molar ratio of the γ-MnO2 precursor to sodium carbonate is 1:(0.18-0.22).
[0044] In the embodiments, the amount of raw materials used strictly follows the defined ratio range; in step S1, the molar ratio of manganese sulfate monohydrate and manganese chloride to sodium thiosulfate is 0.5:0.5:1; this ratio ensures that the redox reaction proceeds fully according to the stoichiometric ratio, manganese ions are completely oxidized and precipitated, and H+ is generated from the decomposition of deionized water. + It can be fully embedded in the precursor structure; if the ratio deviates from this range, it may lead to incomplete manganese precipitation or H +Insufficient content affects the subsequent topological reconstruction effect; in step S2, the molar ratio of γ-MnO2 precursor to sodium carbonate is 1:0.22; this stoichiometric ratio is similar to that of the target product Na. 0.44 The sodium-to-manganese ratio in MnO2 is precisely matched to ensure that the sodium content is just enough to meet the requirements for forming a pure-phase tunnel structure, avoiding the formation of P2 layered impurity phases due to excessive sodium, or the presence of unreacted MnO2 impurity phases in the product due to insufficient sodium.
[0045] In one specific embodiment, in step S1, the microwave reaction temperature is 80℃~120℃, and the reaction time is 1~30min; in step S2, the calcination temperature is 800℃~1000℃, the calcination time is 4~12h, and the heating rate is 1~10℃·min. -1 .
[0046] In step S1, the microwave reaction temperature is 100℃. This temperature ensures sufficient reaction between sodium thiosulfate and manganese sulfate and manganese chloride, while preventing abnormal growth or structural damage of precursor particles due to excessive temperature. The reaction time is 5 minutes. Under microwave-assisted conditions, precursor nucleation and growth can be completed in a short time, with efficiency far exceeding the several hours required by traditional hydrothermal methods. In step S2, the calcination temperature is 900℃. At this temperature, the tunnel structure can fully form good crystals. If the temperature is too low, the solid-phase reaction will be incomplete, while if the temperature is too high, the tunnel structure may collapse or transform into other crystalline phases. The calcination time is 6 hours to ensure sufficient reaction between the precursor and sodium carbonate, completing the H+ reaction. + / Na + The topological reconstruction process; heating rate 5℃·min -1 A moderate heating rate is conducive to uniform phase formation and regular grain growth of the product, and avoids phase separation or abnormal grain growth caused by rapid heating.
[0047] In one specific embodiment, the γ-MnO2 precursor obtained in step S1 contains hydrogen ions; H+ ions are generated during the calcination process in step S2. + / Na + Topological reconstruction due to site competition leads to H in the final product + Selectively occupying electrochemically inert tunneling sites, Na + S-shaped tunneling sites occupying electrochemical activity.
[0048] In step S1, sodium thiosulfate undergoes a redox reaction under microwave heating and in the presence of manganese sulfate and manganese chloride, generating hydrogen ions during the decomposition of deionized water. These hydrogen ions are embedded in the tunnels or interlayer structures of the newly formed γ-MnO2 precursor, making the precursor itself rich in hydrogen ions. In the subsequent high-temperature calcination stage of step S2, this hydrogen-rich precursor... +The precursor reacts with sodium carbonate in a solid-state reaction, triggering a crucial topological reconstruction process; the Na produced by the decomposition of sodium carbonate... + Upon entering the tunnel structure, it interacts with H, which has already occupied an inert tunneling site. + Site competition occurs; due to H + It has a stronger binding affinity to electrochemically inert tunneling sites, H + Will not be Na + Instead of replacing it, Na selectively retains it in these inert sites; this competitive occupancy effect forces Na to... + All ions enter the electrochemically active S-shaped tunneling sites; the entire ion rearrangement process is completed while maintaining the original tunneling structure framework topology, ultimately achieving H... + Selectively occupying electrochemically inert tunneling sites, Na + The ideal crystallographic configuration for occupying the S-shaped tunnel sites that are electrochemically active; in contrast, the traditional oxalic acid method used in the comparative example involves directly mixing and calcining manganese and sodium salts. When sodium ions form tunnel structures, they randomly occupy various sites, and inevitably a large number of sodium ions enter inert sites, making it impossible to achieve the above-mentioned directional site occupancy regulation effect.
[0049] In one specific embodiment, in step S1, the washing is performed by sequentially washing with deionized water and anhydrous ethanol, and the drying is performed by vacuum drying at 60℃~100℃ for 6~24h.
[0050] The precipitate was washed three times each with deionized water and anhydrous ethanol. Deionized water effectively dissolved and removed unreacted inorganic salt ions (such as sulfate and sodium ions), while anhydrous ethanol further washed away organic impurities and reduced the surface tension of the precipitate, preventing particle agglomeration during drying. Drying was carried out in a vacuum oven at a temperature of 80℃ within the range of 60℃ to 100℃, for a drying time of 12 hours within the range of 6 to 24 hours. The vacuum environment lowered the boiling point of water, allowing drying to proceed fully at a lower temperature, avoiding unnecessary oxidation or structural changes of the precursor at high temperatures, ensuring the high purity and structural integrity of the precursor, and providing a qualified intermediate product for subsequent calcination steps.
[0051] A sodium-ion battery positive electrode sheet comprises a positive electrode material, a carbon black conductive agent, and a polyvinylidene fluoride binder. The positive electrode sheet is prepared by mixing the positive electrode material, carbon black, and polyvinylidene fluoride in N-methylpyrrolidone to form a slurry.
[0052] The specific preparation process is as follows: The active material obtained in the example is mixed with carbon black as a conductive agent and polyvinylidene fluoride as a binder, using N-methylpyrrolidone as a dispersion medium, and a uniform electrode slurry is obtained according to conventional mixing and slurry preparation process; the slurry is coated on an aluminum foil current collector, and after vacuum drying, rolling and cutting, a positive electrode sheet that can be used for sodium-ion batteries is obtained; the formulation and preparation process of the positive electrode sheet have been fully applied in the battery assembly of the aforementioned electrochemical performance test; using carbon black as a conductive agent can build a good electronic conductive network between the active material particles; using polyvinylidene fluoride as a binder can ensure a strong bond between the active material and the current collector, and maintain the integrity of the electrode structure during cycling.
[0053] A sodium-ion battery includes a positive electrode, a metallic sodium negative electrode, and an electrolyte, wherein the positive electrode comprises a positive electrode sheet.
[0054] Using the aforementioned positive electrode as the positive electrode and metallic sodium as the negative electrode, along with a glass fiber separator and sodium hexafluorophosphate electrolyte dissolved in carbonate solvents, a complete sodium-ion battery is assembled through a packaging process. In the performance test of the aforementioned embodiment, a coin cell configuration with metallic sodium negative electrode was used to evaluate the material performance, and the defined battery has been directly implemented and verified. In the test, the battery exhibited excellent comprehensive performance with an initial charge capacity of 110.3 mAh / g (0.1C), a capacity of 90.5 mAh / g after 350 cycles at 1C, and a capacity of 74.7 mAh / g at 5C rate, which strongly demonstrates the practical value and commercial potential of the positive electrode material of this invention.
[0055] Comparative Example 1
[0056] First, we provide an example of preparing tunnel-type manganese-based oxides using a traditional solid-state method: This comparative example uses the traditional oxalic acid method to prepare Na 0.44 MnO2 material; manganese acetate and sodium carbonate were dissolved in 4M oxalic acid solution at a molar ratio of 1:0.22 and reacted in a water bath at 60℃ for 3 h. The solution was then evaporated to dryness to obtain a white manganese oxalate precipitate. The precipitate was dried at 60℃ overnight, ground in an agate mortar, and then placed in a muffle furnace at 5℃·min. -1 The heating rate was increased to 900℃ and calcined for 3 hours, then naturally cooled to room temperature in the furnace to obtain conventional Na. 0.44 MnO2 material; when tested in sodium metal coin cells, the capacity of this material was only 60 mAh / g in the first week of charging at 0.1C rate, and the capacity decayed to 23.5 mAh / g after 350 cycles at 1C. The fundamental reason for this result is that in the traditional high-temperature solid-state method, sodium ions randomly occupy the tunnel structure, and a large number of sodium ions enter the electrochemically inert tunnel sites, forming dead sodium that cannot be removed, which severely restricts the release of capacity.
[0057] Application Example 1
[0058] The positive electrode material obtained in Example 1 was used as the active material and mixed with conductive agent carbon black and binder polyvinylidene fluoride in a mass ratio of 8:1:1. An appropriate amount of N-methylpyrrolidone solvent was added, and a uniform slurry was prepared in a homogenizer. The slurry was coated on an aluminum foil current collector, and after vacuum drying, rolling, and cutting, a positive electrode sheet was obtained. A sodium metal sheet was used as the negative electrode, a glass fiber membrane was used as the separator, and a 1M NaPF6 ethylene carbonate / dimethyl carbonate (volume ratio 1:1) solution was used as the electrolyte. The cells were assembled into CR2025 coin cells in an argon-filled glove box. The electrochemical performance was tested at 25°C and a voltage range of 2.0-4.0V.
[0059] The test results are attached. Figure 4 As shown, Figure 4 In this context, H-NMO represents the tunnel-type manganese-based oxide cathode material prepared in Example 1 of this invention; that is, through H... + / Na + Hydrogen ions (H+) prepared by topological reconstruction strategy + Na occupying electrochemically inert tunneling sites 0.44 MnO2 material; Na-NMO represents the conventional tunnel-type manganese-based oxide cathode material prepared in Comparative Example 1, i.e., conventional Na+ prepared by the conventional oxalic acid solid-state method, in which sodium ions randomly occupy various sites. 0.44 MnO2 material; the 57mAh / g marked in the figure means: the double-headed arrows indicate the difference in first-week charging capacity between the material of this invention (red line, first-week capacity approximately 110mAh / g) and the traditional material (blue line, first-week capacity approximately 60mAh / g) at a 0.1C rate; the horizontal axis (X-axis) specific capacity (mAh / g) represents the amount of electricity charged or discharged per unit mass of cathode material (per gram) during charging and discharging; the vertical axis (Y-axis) voltage (V) represents the terminal voltage of the battery during the charging and discharging test; combined with Figure 4 As can be seen, the product of the embodiment achieved a charging capacity of 110.3 mAh / g in the first week, which is much higher than the 60 mAh / g of the comparative example, meeting the requirement of not less than 100 mAh / g; this is a direct effect of the above-mentioned structural features: due to the inert sites being H + With the sodium ions in the S-shaped tunnel fully released, they are freed from the constraint of dead sodium on capacity, allowing the material's theoretical capacity to be fully released for the first time.
[0060] Application Example 2
[0061] The only difference between this application example and application example 1 is that the active material is the conventional Na obtained from Comparative Example 1. 0.44 MnO2 material; all other aspects are the same as in Application Example 1.
[0062] Structural and performance testing
[0063] X-ray diffraction tests were performed on the products of Example 1 and Comparative Example 1; the XRD pattern of the product of Example 1 is attached. Figure 1 As shown, the diffraction peaks are related to Na. 0.44 The MnO2 standard card showed a perfect match, with no impurity phase peaks, indicating the formation of a high-purity tunnel-type crystal structure.
[0064] The product of Example 1 was observed using a scanning electron microscope, and its SEM image is attached. Figure 2 As shown, the product exhibits a uniform rod-shaped morphology and consistent size, which is beneficial for electrolyte wetting and shortens the sodium ion diffusion path.
[0065] Using Application Examples 1 and 2 as examples, electrochemical performance comparison tests were conducted. At a 0.1C rate, the first-week charging capacity of the product in Example 1 reached 100 mAh / g, while that of the product in Comparative Example 1 was only 60 mAh / g. The comparison curves are attached. Figure 4 As shown; During long-cycle testing at 1C rate, the product of Example 1 had a discharge specific capacity of 90.5 mAh / g after 350 cycles, while the product of Comparative Example 1 had decayed to 23.5 mAh / g. The comparison curves are attached. Figure 5 As shown; in the rate performance test, the product of Example 1 achieved a discharge specific capacity of 74.7 mAh / g at a high rate of 5C. A comparison of the rate performance is attached. Figure 3 As shown.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0067] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A tunnel-type manganese-based oxide cathode material, the chemical composition of which is Na 0.44 MnO2, characterized in that, The cathode material has a tunnel structure in which hydrogen ions (H+) can pass through. + Sodium ions (Na) occupy electrochemically inert tunneling sites. + It occupies the S-shaped tunneling sites that are electrochemically active.
2. The cathode material according to claim 1, characterized in that, The cathode material has a first-week charging capacity of no less than 100mAh / g at a 0.1C rate.
3. The cathode material according to claim 1 or 2, characterized in that, The discharge specific capacity of the cathode material after 350 cycles at 1C is not less than 85mAh / g.
4. A method for preparing the tunnel-type manganese-based oxide cathode material according to any one of claims 1 to 3, comprising the following steps: S1. Water-soluble manganese salt and thiosulfate are dissolved in water to form a mixed solution, and the reaction is carried out under microwave radiation. After the reaction is completed, the precipitate is separated, washed and dried to obtain γ-MnO2 precursor. S2. The γ-MnO2 precursor is ground and mixed with a sodium source, and then calcined at 700℃~1100℃ in an oxygen-containing atmosphere. After cooling, the cathode material is obtained.
5. The method according to claim 4, characterized in that, In step S1, the water-soluble manganese salt is manganese sulfate monohydrate and manganese chloride, the thiosulfate is sodium thiosulfate, and the molar ratio of water-soluble manganese salt to thiosulfate is 1:(0.8-1.2); in step S2, the sodium source is sodium carbonate, and the molar ratio of γ-MnO2 precursor to sodium carbonate is 1:(0.18-0.22).
6. The method according to claim 5, characterized in that, In step S1, the microwave reaction temperature is 80℃~150℃, and the reaction time is 1~30min; in step S2, the calcination temperature is 800℃~1000℃, the calcination time is 4~12h, and the heating rate is 1~10℃·min. -1 .
7. The method according to claim 6, characterized in that, The γ-MnO2 precursor obtained in step S1 contains hydrogen ions; H+ ions are generated during the calcination process in step S2. + / Na + Topological reconstruction due to site competition leads to H in the final product + Selectively occupying electrochemically inert tunneling sites, Na + S-shaped tunneling sites occupying electrochemical activity.
8. The method according to claim 7, characterized in that, In step S1, the washing is performed by sequentially washing with deionized water and anhydrous ethanol, and the drying is performed by vacuum drying at 60℃~100℃ for 6~24h.
9. A sodium-ion battery positive electrode, characterized in that, The positive electrode sheet comprises the positive electrode material according to any one of claims 1 to 3, carbon black conductive agent, and polyvinylidene fluoride binder, and is prepared by mixing the positive electrode material, carbon black, and polyvinylidene fluoride in N-methylpyrrolidone to form a slurry.
10. A sodium-ion battery, comprising a positive electrode, a metallic sodium negative electrode, and an electrolyte, characterized in that, The positive electrode comprises the positive electrode sheet as described in claim 9.
